2020
DOI: 10.1083/jcb.201903176
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of lysosomes to plasma membrane initiates radiation-induced apoptosis

Abstract: Diverse stresses, including reactive oxygen species (ROS), ionizing radiation, and chemotherapies, activate acid sphingomyelinase (ASMase) and generate the second messenger ceramide at plasma membranes, triggering apoptosis in specific cells, such as hematopoietic cells and endothelium. Ceramide elevation drives local bilayer reorganization into ceramide-rich platforms, macrodomains (0.5–5-µm diameter) that transmit apoptotic signals. An unresolved issue is how ASMase residing within lysosomes is released extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…Since lysosomes are constantly recycling to the plasma membrane, the ASM can be also found on the cell surface and binds to the outer leaflet of the plasma membrane [14][15][16]. Surface ASM acts as a signaling molecule and generates ceramide in the outer leaflet of the cell membrane [14][15][16][17]. Ceramide molecules are very hydrophobic and spontaneously associate with each other to form small ceramideenriched membrane domains that fuse and form large highly hydrophobic, tightly packed, and gel-like ceramide-enriched membrane domains termed "platforms" [14,18,19].…”
Section: The Acid Sphingomyelinase/ceramide Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Since lysosomes are constantly recycling to the plasma membrane, the ASM can be also found on the cell surface and binds to the outer leaflet of the plasma membrane [14][15][16]. Surface ASM acts as a signaling molecule and generates ceramide in the outer leaflet of the cell membrane [14][15][16][17]. Ceramide molecules are very hydrophobic and spontaneously associate with each other to form small ceramideenriched membrane domains that fuse and form large highly hydrophobic, tightly packed, and gel-like ceramide-enriched membrane domains termed "platforms" [14,18,19].…”
Section: The Acid Sphingomyelinase/ceramide Systemmentioning
confidence: 99%
“…These large, distinct, ceramide-enriched membrane domains serve to cluster, aggregate and reorganize activated receptor molecules such as CD95, CD40, DR5 or β1-integrin, to name a few [14,[20][21][22][23][24]. Ceramide-rich platforms were also shown to mediate a variety of stress stimuli such as γ-irradiation [17,25], ultraviolet light [26], or Cu 2+ intoxication [27], as well as infection of cells with at least some pathogenic bacteria and viruses [15,28]. The high density of activated receptors upon trapping and clustering in ceramide-enriched membrane domains and the proximity to signaling molecules facilitates and amplifies signaling via the specific receptor, as shown for CD95 [29].…”
Section: The Acid Sphingomyelinase/ceramide Systemmentioning
confidence: 99%
“…Recently, Ferranti et al, confirmed activation of acid sphingomyelinase, generation of ceramide at the plasma membrane a few minutes after γ-irradiation and a dose and time-dependent induction of apoptosis in hematopoietic Jurkat cells [ 323 ]. Electron microscopic analysis showed that the first step after IR exposure (10 Gy) consisted of the formation of nanopore-like structures in the plasma membrane due to lipid peroxidation leading to calcium entry, initiation of lysosome fusion and subsequent apoptosis (40–50% at 24 h post-irradiation).…”
Section: Ionizing Radiation (Ir) Effects Involving Mitochondriamentioning
confidence: 99%
“…Additionally, lysosomes can undergo exocytosis in response to anti-cancer agents [68]. For instance, recent work demonstrated a calcium-dependent fusion of lysosomes with the plasma membrane following ionizing radiation [69].…”
Section: Lysosome-induced Cell Deathmentioning
confidence: 99%